Microbial community and its potential as descriptor of environmental status. (19th June 2016) - Caruso, Gabriella; Azzaro, Maurizio; Caroppo, Carmela; Decembrini, Franco; Monticelli, Luis Salvador; Leonardi, Marcella; Maimone, Giovanna; Zaccone, Renata; La Ferla, Rosabruna
Abstract: Planktonic communities hold a relevant role within the EU Marine Strategy Framework Directive (MSFD). In view of reaching the Good Environmental Status of marine ecosystems, within this Directive the phyto- and zooplanktonic communities have received great attention, while Prokaryotes (Bacteria, Archaea, and Cyanobacteria) have been neglected. Indeed, the relevance of microbes (particularly of the faecal pollution indicators) as water quality indicators, the role that microorganisms play within the biogeochemical fluxes and in the whole ecosystem functioning, are all important features that deserve to be focused within the MSFD. The present study aims at reviewing the main issues where prokaryotic variables find useful application as descriptors of environmental status, trying to develop a panel of prokaryotic indicators suitable for the environmental quality assessment. From a survey of scientific literature and on field datasets, prokaryotic abundance and activities (enzymatic hydrolysis, prokaryotic production, and respiratory rates) are here chosen as early warning sentinels to detect changes in environmental quality, using an integrated approach with trophic (chlorophyll- a, particulate and dissolved organic matter) measurements.